Penanggulangan Kemiskinan di Afdeeling Demak dan Grobogan 1900-1930: The Overcoming of Poverty in Afdeeling Demak and Grobogan 1900-1930 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This research aims to: (1) make description about indigenous people's living standard condition in Demak and Grobogan, (2) to give some explanation about government's policy to increase their living standard condition and (3) to make a measure of impact the policy had on the indigenous living standard condition Demak and Grobogan area. This research is a historical study using some sources from colonial and local document sourcess. Data is analyzed with political economy approach and simple quantification. Data synthesis use narrative explanation model. Research finding shows that Demak and Grobogan people's ivingstandard condition in XIX century was low. Especially from the beginning to third decade of )0( century local and colonial government made some policies to increase the prosperity of the people in this area. There were physical constructions like dam, canal, public water, road and bridge, and non physical facilities like healthy care, people's credit, and village schools. Those policies have impact on the living standard living to the people in Demak and Grobogan. Agricultural productions, especially rice increased significantly, although land,s control was decreased. People's income per capita also increased, booth in Demak and Grobogan, but in Demak was better than in Grobogan. Income per capita from Demak people was above poverty line, but Grobogan people was still beneath. People's also had another job outside agricultural sector. Health care policy had decreased the victim and death rate, but the death rate of this area was still higher than average Semarang residency. Educated people's was not to many, but the percentage was still more than average Semarang residency. The landing of credit bank was become usual for the people aimed to increase agricultural production and consumptive need.